Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Nu Green Tea Di Kota Batam - Nainggolan, Nora Pitri (Jurnal PROFITA : Akuntansi dan Manajemen, 2022)
This research aims to test and analyze the influence of product diversity, and product quality on purchasing decisions on NU Green Tea products in Batam City. Data collection is done by distributing questionnaires with a sample number of 140 respondents. The research data used is statistical data in the form of multiple regression analysis. Test results t show the value of product diversity with sig 0,002 <0,05 This means that product diversity has a significant influence on purchasing decisions. Test results t show the quality value of the product with sig 0.002 <0.05 This means that the quality of the product has a significant effect on purchasing decisions. While the test results F shows the value 125.663> 9.978 with sig 0,000 <0,05, so that simultaneously the variables of product diversity and product quality have a significant effect on purchasing decisions.